The Effect of Internal Pressure on Radial Strain of Steel Pipe Subjected to Monotonic and Cyclic Loading - Pleșcan, Costel; Stanciu, Mariana D.; Szasz, Matyas (MDPI AG, 2019)
During loading, certain mechanical and chemical phenomena develop inside the pipes and cause them to burst. In this study, the inﬂuence of internal pressure on the elastic and plastic behaviour of E355 steel pipes was investigated on small specimens with di erent wall thicknesses. First, the failure modes of pipes subjected to monotonic loading were assessed, and then the behaviour of specimens subjected to cyclic internal pressure was analysed in terms of variation of radial strain. The strain and stress states of pipes were analysed using the ﬁnite element method. The results revealed that the hardening of materials inside the pipes increases the risk of cracking and bursting because of elasticity limits being exceeded, causing entry into the plastic domain. The transition of mechanical behaviour can be observed in the microstructure of steel in cracked areas from the inside to the outside of the pipe.